Acute pancreatitis in rheumatology practice, with emphasis on systemic lupus erythematosus: A case series and newer concepts - Praveen Pratap Jadhav; Saourabh Rajesh Desai; Janhavee Praveen Jadhav; Lata Sunil Bichile (Indian Journal of Rheumatology)
Acute pancreatitis is seen in many rheumatological disorders, of which, systemic lupus erythematosus (SLE) is the most common. SLE is a multisystemic disease, affecting the gastrointestinal system in about half of the patients. Acute pancreatitis is a rare but life-threatening complication of SLE. Here, we report three intriguing cases of SLE wherein patients suffering from SLE presented with acute pancreatitis either as the initial symptom of the disease or as a flare. Another patient in this series is of dermatomyositis. Literature is reviewed, and newer concepts are discussed.